Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada CV. Sinar Utama Di Tenggarong - Sugeng Raharjo (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2015)
CV. Main beam engaged in the selling dealer of Yamaha brand motorcycles, the street address KH Akhmad Muksin 5 Rt.26 Ex. Timbau Tenggarong under the leadership of Mr. Rudiansyah need to pay attention to the services provided to consumers, in order to make consumers satisfied with the services rendered. Observations researchers, CV. Main beam has been serving its customers with a good attempt, but from the responses of consumers, they still do not feel comfortable and less well served to consumers, so as consumers are reluctant to return it to buy goods there because the service is still less than the maximum by employees CV. Main beam. The purpose of this study was to determine the influence of variables Reliability, Responsivennes, Assurance, Empathy and Tangible against kepusan consumers in CV. Main beam in Tenggarong and to determine which variables are mempunnyai most dominant influence on consumer satisfaction in CV. Main beam in Tenggarong. Keywords: Service, Satisfaction